The Autumnal Imagination: Temporality and Transience in Keats’ Landscape Poetry - Ghosh, Risha; Mukhopadhyay, Papri (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
This study explores how John Keats showed the nature of temporary life through his autumn landscape writing. Our close analysis of "To Autumn" shows how Keats uses the autumn theme to explore the deeper meanings of human existence and the reality of aging and death. This research examines how "Ode to a Nightingale" displays human mortality through its thematic analysis of different objects. In these poems Keats compares temporary human life with eternal nature cycles to probe deep thoughts about human existence. Spring and autumn stand as more than regular seasons in Keats's work because his poetry reflects on human life's changes while showing the people's need to live forever. The study adds to academic discussions through its examination of Romanticism's deep examination of nature and time linked to mortality.